A novel numerical method to evaluate the thermal conductivity of the unidirectional fiber‐reinforced composites. Issue 9 (25th July 2022) - Cai, Heng; Ye, Junjie; Xi, Jiale; Hong, Yun; Shi, Yang; Wang, Yongkun; He, Wangpei
Abstract: In this study, an effective microscale method based on the parametric modeling scheme of the finite volume method is improved to evaluate the effective thermal conductivity and localized thermal fields of the fiber‐reinforced composites. By comparing with the finite element method and experimental data, it is indicated that the proposed microscale method exhibits a high accuracy in solving their effective properties. On this basis, the mesh sensitivity and fiber volume fraction influence on the thermal conductivity are both investigated. The number of 36 × 36 sub‐cells is employed as the RVE model to balance the computational efficiency and simulating accuracy. In addition, affected by the thermal conductivity and microstructure of constituent materials, the heat flux distribution near the interface between phenolic resin matrix and glass fiber is relatively uniform. The study on the influencing factors of the volume fraction shows that the equivalent thermal conductivity increases slowly at the low volume fraction, while the growth rate of the equivalent thermal conductivity increases significantly at the high‐volume fraction. Abstract : Employing numerical method to evaluate thermal conductivity of composites